Assessment of landslides susceptibility in Serra do Mar by application of physiographic compartmentalization - Gabelini, Beatriz Marques [UNESP]; Dos Santos Corrêa, Claudia Vanessa [UNESP]; Cerri, Rodrigo Irineu [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP]; Zaine, José Eduardo [UNESP]; Do Carmo Giordano, Lucília [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
The study area is in Caraguatatuba and São Sebastião municipalities, in the north coast of the state of São Paulo, Brazil. The area presents high potential for landslides occurrence because it is in the domain of Serra do Mar, with steep relief associated with the high rainfall index of the region. Thus, analyzes aimed at the recognition and greater understanding of conditioning factors and natural phenomenon, such as landslides, are of great importance in avoiding damages and risks from the prediction of such phenomenon. The aim of this research is to assess the susceptibility to landslides through the application of physiographic compartmentalization of the coast and mountain region of Caraguatatuba and São Sebastião municipalities, in the State of São Paulo, Brazil. For this, photoanalysis techniques and photointerpretation of aerial images were used, which allowed the division of the area into smaller units, according to similar physiographic characteristics, which favored the choice of factors conditioning the occurrence of landslides. In addition, landslide scars maps were also used in two different periods (1976 and 2011). The association of the landslides scars map with the physiographic compartmentalization analysis was fundamental for the elaboration of this research, since it validated the information acquired by the compartmentalization and determined the weights of the conditioning factors in the susceptibility map. The results showed that, among sixteen units, the physiographic units with high susceptibility — IV, V, VI, VIII, IX and XII — exhibited a predominantly high slope (> 30º), a large local amplitude (over 300 m) and gneisses and migmatites rocks.
Avaliação da suscetibilidade a escorregamento na Serra do Mar pela aplicação da compartimentação fisiográfica
Keywords: Landslides; Physiographic compartmentalization; Scars inventory; Serra do mar; Susceptibility